Developing a visual rhetoric conceptual framework for Public Service Announcements (PSAs) advertising campaigns / Nur Safinas Albakry - Albakry, Nur Safinas (Institute of Graduate Studies, UiTM, 2016)
The visual rhetoric is an important element to increase the effectiveness of the process of information exchange. In fact, visual rhetoric helps to get messages across to the intended audience in a persuasive way. Visual rhetoric is described as a form of communication that uses images for creating meaning or constructing an argument. Hence, an analysis of visual rhetoric considers how images work alone and collaborate with other elements to create an argument designed for moving a specific audience Bulmer & Oliver (2006, p.55). Visual rhetoric in visual advertising involves how the audience choose to present information or argument through images. A key concept of visual rhetoric study in Malaysia Public Service Announcements (PSAs) contexts use focuses on how rhetorical figures in Public Service Announcements (PSAs) could convey to react and response in visual arguments by developing a persuasive message into a great communication process. The purpose of this study is to explore and discuss the understanding of rhetorical theories by implementing the visual rhetoric in print advertising on how visual arguments can affect consumers processing and response toward persuasive forms message. The aim of this study is to propose a framework system model for the effective use of visual content in the visual advertising communication process in Malaysia that could be employed by visual rhetoric in print media to instil advertising awareness…